2019
DOI: 10.3847/2041-8213/ab4992
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Particle Acceleration in the Wolf–Rayet Bubble G2.4+1.4

Abstract: The supersonic winds produced by massive stars carry a large amount of kinetic power. In numerous scenarios such winds have been proven to produce shocks in which relativistic particles are accelerated emitting non-thermal radiation. Here, we report the first detection of non-thermal emission from a single stellar bubble, G2.4+1.4, associated with a WO star. We observed this source with the uGMRT in Band 4 (550 − 850 MHz) and Band 5 (1050 − 1450 MHz). We present intensity and spectral index maps for this sourc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
0
14
1
Order By: Relevance
“…Wolf-Rayet nebulae entered the X-rays domain with Asca (Wrigge et al 2005) Rosat and Chandra (Guerrero & Chu 2008), XMM-Newton (Toalá et al 2012) observations from their (shocked) stellar winds witnessing emission of optically-thin high temperature plasma. More recently, a radio non-thermal synchrotron counterpart of the stellar wind bubble of a Wolf-Rayet ring nebula indicated that these circumstellar nebulae are the site of particles accelelration (Prajapati et al 2019). This accumulation of observations motivates the present numerical efforts aiming at understanding the peculiar vicinity of young Wolf-Rayet stars.…”
Section: Introductionmentioning
confidence: 93%
“…Wolf-Rayet nebulae entered the X-rays domain with Asca (Wrigge et al 2005) Rosat and Chandra (Guerrero & Chu 2008), XMM-Newton (Toalá et al 2012) observations from their (shocked) stellar winds witnessing emission of optically-thin high temperature plasma. More recently, a radio non-thermal synchrotron counterpart of the stellar wind bubble of a Wolf-Rayet ring nebula indicated that these circumstellar nebulae are the site of particles accelelration (Prajapati et al 2019). This accumulation of observations motivates the present numerical efforts aiming at understanding the peculiar vicinity of young Wolf-Rayet stars.…”
Section: Introductionmentioning
confidence: 93%
“…For a typical WR lifespan (through the WC or WO phase) of ∼ 5 × 10 5 yr, and a maximum wind power of 10 38 erg s −1 (e.g. Prajapati et al 2019), one obtains E winds ∼ 1 × 10 51 erg, comparable to E SN . Mass loss rates for WR stars are 10 −5 M yr −1 (Crowther 2007) and with the total fraction of 12 C + 16 O being on the order of 0.65 (e.g.…”
Section: Constraints On the Radiation Environmentmentioning
confidence: 99%
“…We can learn more about the relativistic particle population by fitting the observed spectrum with a nonthermal emission model. We follow a similar approach as in Prajapati et al (2019) and model the non-thermal electron distribution as a power law with a spectral index p = 2.6, with a hardening at E e < 10 MeV due to ionization losses, and a high-energy cutoff at ∼ 100 GeV produced by synchrotron losses. The particle distribution normalization is set by the condition U NT = η mag U mag , with U NT the energy density in relativistic particles and η mag is a parameter in the range 3 × 10 −3 -0.75 (in accordance to the allowed range for B).…”
Section: Non-thermal Emission In S305mentioning
confidence: 99%